Systems modeling of a phenazine-producing Escherichia coli bio-battery anolyte - Simon M. King; Michael R. King (PLoS ONE, 2026)
Bioelectrochemical systems that combine living microbes with electrochemical devices are emerging as platforms for sustainable energy and chemical production. Phenazine-based organic redox flow batteries (RFBs) already achieve high-capacity, long-lived negolytes, but their performance is limited by electrolyte degradation. Recent work has demonstrated that genetically engineered, phenazine-producing Escherichia coli can regenerate degraded anolyte species in an operating RFB, suggesting a new class of “bio-batteries.” However, there is little quantitative understanding of how microbial physiology, phenazine toxicity, and electrochemical operating conditions jointly constrain performance. Here we develop a zero-dimensional mechanistic model that couples an engineered E. coli chassis to a phenazine-based flow battery half-cell. The microbial module includes Monod-type substrate uptake, growth-associated phenazine biosynthesis, first-order phenazine degradation, and a Hill-type toxicity term informed by pyocyanin’s micromolar-scale inhibitory effects. The electrochemical module computes Nernstian anode potentials from reduced/oxidized phenazine, adds a lumped area-specific resistance, and explicitly simulates charge discharge cycles with voltage cut-off criteria. We then sweep phenazine production strength, initial biomass loading, toxicity, and mediator stability to map the design space. The model predicts a strong trade-off between instantaneous current density and long-term capacity: high phenazine production and biomass can briefly reach 1.5 × 10 −3 mA·cm ⁻ ² current densities but rapidly trigger toxicity-driven collapse, whereas more conservative designs deliver low current over an extended time period. When embedded in a simple RFB cycling protocol, moderate-production designs converge to a quasi-steady discharge capacity that is far below that of state-of-the-art phenazine RFBs, but exhibit partial self-regeneration of mediator capacity across cycles. Our results quantify the fundamental constraints of phenazine-based microbial anolytes and highlight engineering priorities, such as enhanced host tolerance and low-toxicity mediators, required for bio-batteries to become competitive or to occupy niche low-power, self-regenerating roles.